Factors associated with instrumental activities of daily living functional capacity in brazilian older adults (Research, Society and Development, 2021)
Introduction: Functional capacity decrease in instrumental activities of daily living, which allows the independence to participate in the community, can be related to the aging process. The evaluation of these activities seems to be more sensitive to initial processes in changes on the functional capacity of the older adults. Objective: To analyze factors associated with instrumental activities of daily living functioning in Brazilian older adults’ population. Methods: Data from people over ≥ 60 years old who participated in the National Health Survey 2013 were used. The outcome variable was “Functional capacity in instrumental activities of daily living”. As independent variables, sociodemographic, health and lifestyle and cardiovascular risk were used. For statistical analysis, multiple linear regression for complex samples was used. Results: It was included 11.177 participants. A significant association for both genders was observed between “Functional Capacity in instrumental activities of daily living” and the variables “Age”, “Marital status”, “Health perception”, “Falls in the last 12 months”, “Alcohol consumption” and “Level of Physical Activity”. “Systolic High blood pressure” was only for females. Conclusions: Several conditions were related to the functional capacity in the older population including sociodemographic, health and lifestyle, and cardiovascular risk.